Effect of the Common Agricultural Policy on Agriculture and the Increasing Role of Nongovernmental Organisations - Zdanovskis, Kristaps; Pilvere, Irina (Socialiniai tyrimai, 2018)
The Common Agricultural Policy (CAP) has considerably contributed to changes in the rural environment of Latvia after its accession to the European Union (EU). The accession provided new opportunities and considerable financial support for agriculture, yet the competition of farms under the conditions determined by the CAP has changed the composition of final agricultural output in Latvia. As the number of EU Member States increased and the CAP became more complicated, an increasing role in defending the interests of farmers is played by farmer organisations.